Food allergy issues among consumers: a comprehensive review - Sansweet, Samantha; Jindal, Ria; Gupta, Ruchi (Frontiers in Nutrition, 2024)
Food Allergy (FA) is a growing global public health concern. In the United States alone, 8% of children and 11% of adults have a convincing FA (symptoms of specific allergens consistent with an IgE-mediated reaction to a specific allergen). Given the significant prevalence of this condition, the objective of this mini-review is to illustrate the many dimensions of life that are impacted among those with FA. Summarizing findings from a breadth of current literature, we present how FA affects social, psychological, and economic-related quality of life. With this informative review, we endeavor to bring increased awareness to these issues and help cultivate a better future for individuals with FA.